Innocent in Death - Book 24 - Robb, J. D., 1950- (New York : G.P. Putnams Sons, 2007)
Investigating the baffling murder case of an ordinary and much-loved private school teacher, New York City lieutenant Eve Dallas struggles to identify who may have wanted the death of an innocent man.
Keywords: Dallas, Eve -- (Fictitious character); Fiction; Police -- New York (State); New York; Fiction; Teachers -- Juvenile fiction; New York (N.Y.) -- Fiction; Fiction